THE COVID-19 PANDEMIC: ITS IMPACTS ON STUDENTS’ DIGITAL CAPABILITIES - Rini, Sri Endah Setia; Herusatoto, Hesthi; Hapsari, Hilaria Dewi (Conscientia - Journal on Language, Literature, and Culture, 2023)
The Covid-19 Pandemic has affected human life in various aspects. Study and work in the year of 2020 to 2021 had to be done fully online. This condition has pushed people to improve their digital skills so that they could continue working, learning, and communicating efficiently and effectively in any situation. Digital capability should indeed be developed because it has become a requirement for any endeavor in the future. Students have been among those whose digital skills must be upgraded. The pandemic has forced them to increase their digital capabilities. This research was conducted to determine digital literacy of STBA LIA Yogyakarta students pre- and post-the Covid-19 pandemic. Ninety (90) students filled out a survey concerning their digital skills before and after the pandemic. This quantitative descriptive research was to see the increase in the 5 elements of student digital capabilities as proposed by JISC. The findings showed that students' abilities in the five elements have improved quite a lot. The number of students with ‘good; and ‘very good’ abilities increased and the number of students with ‘weak’ and ‘very weak’ abilities decreased. Students with ‘good’ and ‘very good’ abilities after the pandemic were evenly distributed across four elements. A slight increase was indicated in the digital creation, problem solving and innovation abilities, albeit still in the ‘average’ category both before and after the pandemic.